Pathogen-induced physiological reprogramming and systemic dysfunction in plants - Mubashir Sharif; Muhammad Annas Shahid; Mahad Ur-Rehman; Ikhlas Shafique; Muhammad Farooq; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2026)

Enhancing Circularity in the Construction Industry: Life Cycle Assessment of Recycled Fibers in Concrete Composites - Alberto Pietro Damiano Baltrocchi; Muhammad Shafique; Vincenzo Torretta (Waste Management, 2026)

Integrated multi-hazard vulnerability and risk assessment in the Hindu Kush Mountains of Northern Pakistan: Challenges and recommendations - Muhammad Shafique; Alamsher Bacha; Muhammad Waseem; Zahra Hassan; Muhammad Asif Khan; Lewis A. Owen (Geomorphology, 2026)

Structural and physiological adaptations conferring herbivory resistance in wild olive (Olea europaea L. subsp. cuspidata) - Faakeha Islam; Syed Mohsan Raza Shah; Farooq Ahmad; Mansoor Hameed; Sana Basharat; Sana Fatima; Ansar Mehmood; Zahida Parveen; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2026)

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Integrated probabilistic seismic hazard and risk assessment of Hunza District, northern Pakistan - Muhammad Waseem; Muhammad Shafique; Waqas Ahmed; Sarfraz Khan (Bulletin of Earthquake Engineering, 2026)

Nanopriming with biogenic selenium nanoparticles restores physiological performance and antioxidant defense in salt-stressed maize cultivars - Hummera Nawaz; Amina Ameer; Ameer Khan; Anees Manzoor; Muhammad Jamil; Saima Shafique; Ansar Mehmood; Khawaja Shafique Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Assessment of functional trait variation in arid-zone plant families to evaluate indicator species for rehabilitation of degraded landscapes - Eisha Kanwal; Farooq Ahmad; Ansa Asghar; Ummar Iqbal; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Saba Gul; Muhammad Irshad; Khawaja Shafique Ahmad (The Science of Nature, 2026)

Environmental KPI Reporting in Ports: Patterns, Gaps, and Opportunities for Systemic Change - Seyedeh Azadeh Alavi-Borazjani; Muhammad Noman Shafique; Zeeshan Arshad (International Journal of Environmental Research, 2026)
Ports play a critical role in global sustainability transitions, yet environmental performance reporting remains fragmented and uneven. This study examines environmental key performance indicator (KPI) reporting practices across twenty-five benchmark ports using a multi-category framework encompassing major environmental dimensions. The analysis reveals that, while most ports have established baseline transparency and compliance with international standards, reporting predominantly focuses on inventory-based and infrastructure-oriented indicators, with limited tracking of outcome-oriented performance metrics such as progress toward emissions reduction targets or reductions in stormwater pollution loads. Performance-based, outcome-oriented, and integrative KPIs remain underrepresented across environmental domains. High-level sustainability commitments are frequently disclosed without systematic progress tracking, and environmental domains are often reported in isolation, limiting holistic planning and comparability. Emerging areas such as climate risk assessment, environmental finance, acoustic management, and regenerative design exhibit particularly low reporting maturity. These findings underscore the need to shift from descriptive, compliance-driven disclosures toward harmonized, integrated KPI frameworks that support performance evaluation, strategic decision-making, and systemic sustainability transformation in the global port sector.

Erratum to: Tree Age-Dependent Modulation of Fruit Endogenous Hormones and Quality Attributes in ‘Kinnow’ Mandarin (Citrus nobilis × C. Deliciosa) - Khadija Bibi; Kashif Razzaq; Ishtiaq Ahmad Rajwana; Ambreen Naz; Muhammad Shafique Khalid (Applied Fruit Science, 2026)

A novel multi-epitope mRNA vaccine against Escherichia coli using an in silico reverse vaccinology approach - Shakeela Parveen; Javeria Abbasi; Muhammad Hussain; Muhammad Farhan Khan; Muhammad Tayyab; Amina Parveen; Laiba Shafique (Journal of Applied Genetics, 2026)

Lifecycle emissions of hydrogen supply chains in China: A spatially resolved assessment - Fangjie Liu; Muhammad Shafique; Xiaowei Luo (Environmental Impact Assessment Review, 2026)

Nutritional profile, phytochemicals, and bioactivities of the Himalayan herbal tea plant Persicaria amplexicaulis - Amna Mustafa; Ansar Mehmood; Imtiaz Hussain; Muhammad Imran Hamza; Khawaja Shafique Ahmad; Mushtaq Ahmad (Plant Biosystems, 2026)

Tree Age-Dependent Modulation of Fruit Endogenous Hormones and Quality Attributes in ‘Kinnow’ Mandarin (Citrus nobilis × C. deliciosa) - Khadija Bibi; Kashif Razzaq; Ishtiaq Ahmad Rajwana; Ambreen Naz; Muhammad Shafique Khalid (Applied Fruit Science, 2026)

Correction to: Structural and functional traits governing the adjustments, survival, and success of C₄ grasses in arid and semi-arid environments - Marwah Saif; Farooq Ahmad; Jazab Shafqat; Ummar Iqbal; Ansa Asghar; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad (Plant and Soil, 2026)

Precision harvest: path to genetically modified organism-free crops with CRISPR by 2035 - Sunny Ahmar; Ruixiang Zhang; Pouneh Pouramini; Anna Janeczko; Muhammad Sohaib Shafique; Marcin Rapacz; Rodrigo S. Reis; Qinlong Zhu; Goetz Hensel; Ewa Pociecha (Trends in Plant Science, 2026)

Structural and functional traits governing the adjustments, survival, and success of C₄ grasses in arid and semi-arid environments - Marwah Saif; Farooq Ahmad; Jazab Shafqat; Ummar Iqbal; Ansa Asghar; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad (Plant and Soil, 2026)

Impacts of climate change and local stressors on the coral community structure off the eastern coast of Pakistan - Amjad Ali; Azka Rafiq Malik; Naveed Ahmad; Gulab Said; Zulfiqar Ali Mirani; Seema Shafique; Habibul Hassan; Ateeque Rahman Khooharo; Faiz Muhammad (Regional Studies in Marine Science, 2026)

From snowmelt to disaster: modeling debris flow dynamics in the Shatoobar Nala watershed, Hunza, Pakistan - Hameed Ullah Khan; Muhammad Shafique; Javeria Aftab; Uzair Zahid; Ihsan Ullah (Natural Hazards, 2026)

Molecular characterization and gene expression of the HSP90 gene family in Cyprinus carpio and Oreochromis niloticus under thermal stress - Shakeela Parveen; Mehwish Sultana; Muhammad Tayyab; Muhammad Farhan Khan; Muhammad Hussain; Amina Parveen; Youhou Xu; Peng Zhu; Laiba Shafique (Fish Physiology and Biochemistry, 2026)

Molecular pathways in plant growth-promoting rhizobacteria–plant interactions: a comprehensive review - Muhammad Faiq Irfan; Shazia Shafique; Sobiya Shafique; Bushra Tabassum; Allah Rakha Yaseen (Archives of Microbiology, 2026)

Cost-effective phosphorous recovery from distillery wastewater using inherent nutrients: agronomic and economic assessment - Raffia Siddique; Muhammad Ansar Farooq; Munib Ahmed Shafique (Environment, Development and Sustainability, 2026)

Trait dynamics of endemic Festuca species reveal cold-resilience across elevation gradient - Khawaja Shafique Ahmad; Syed Mohsan Raza Shah; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Ummar Iqbal; Ansar Mehmood; Sana Fatima; Wisal Muhammad Khan; Muhammad Ashraf; Hazem M. Kalaji; Manzer H. Siddiqui (Acta Physiologiae Plantarum, 2026)

Study of Molecular Docking and Evolutionary Dynamics of the FGF Gene Family in Nile Tilapia - Muhammad Farhan Khan; Shakeela Parveen; Muhammad Abdul Manan; Fariha Latif; Alfabetian Harjuno Condro Haditomo; Youhou Xu; Peng Zhu; Laiba Shafique (Marine Biotechnology, 2026)

A Conserved Bactericidal Permeability-Increasing Protein (BPI) Mediates Immune Sensing and Host Defense in the Hong Kong Oyster (Crassostrea hongkongensis) - Laiba Shafique; Yuwei Zhao; Muhammad Farhan Khan; Cheng Huang; Li Li; Peng Zhang; Peng Zhu; Da Zeng; Xueyu Yan; Bin Gong; Yongyan Liao; Youhou Xu; et al. (Fishes, 2026)
The bactericidal permeability-increasing protein (BPI) and lipopolysaccharide binding protein (LBP) are fundamental to innate immunity. However, their functional diversity and evolutionary conservation in ecologically crucial invertebrates, such as oysters, remain largely understudied. In this study, we identify and characterize a novel homolog of BPI/LBP, designated as ChBPI/LBP in the Hong Kong oyster (Crassostrea hongkongensis). Through structural and phylogenetic analysis, we identify ChBPI/LBP as a distinct member of the BPI protein family, with a high isoelectric point (pI of 9.26), indicating potent cationic BPI-like bactericidal function. We found that ChBPI/LBP is constitutively highly expressed at mucosal sites such as the gills and is rapidly upregulated in hemocytes following a challenge with Aeromonas hydrophila. Recombinant ChBPI/LBP demonstrated potent and specific bactericidal activity against Gram-negative pathogens. These findings suggest that ChBPI/LBP is an important antimicrobial peptide (AMP) effector in the oyster’s immune response. This work provides novel perspectives on the evolutionary mechanisms of innate immunity in bivalves and may have implications for disease management in aquaculture.

Ecological Insights into Plant Diversity and Distribution Along Environmental Gradients in Haveli Kahuta, Pakistan - Syed Tahir Hussain Bukhari; Khawaja Shafique Ahmad; Muhammad Tayyib Riaz; Majid Mahmood Tahir; Ansar Mehmood; Ummar Iqbal; Tajmal Imtiaz; Hazem M. Kalaji; Manzer H. Siddiqui (Environmental Monitoring and Assessment, 2026)

National-scale land suitability assessment for eucalyptus plantation in Pakistan using analytic hierarchy process (AHP) and geospatial modeling - Faisal Khalid; Sami Ullah; Muhammad Shafique; Majid Hussain (Forest Ecology and Management, 2026)

Dual-interface MXene engineering for low-noise perovskite photodetectors in optical communication and health monitoring - Shareen Shafique; Haodong Wang; Yegang Lu; Taimoor Iqbal; Yuheng Wang; Baihui Shen; Ran Zhao; Li Sheng; Cheng Yang; Muhammad Sulaman; Fei Zheng; Ziyang Hu (Chemical Engineering Journal, 2026)

Multi-scale debris flow risk assessment using morphometrics in high-altitude catchments of Northern Pakistan - Yaseen Ullah; Muhammad Shafique; Nisar Ali Shah; Ghazanfar Ali Khattak; Sajid Ullah (Natural Hazards, 2026)

Silver nanoparticle-formulate of an Ailanthus altissima leaf extract as an effective fungicide against Pythium myriotylum, a causative agent of damping off of chili - Urooj Bashir; Ansar Mehmood; Abd ur Rehman Khalid; Muhammad Abdul Rauf Khan; Khawaja Shafique Ahmad; Javaria Khatoon; Nayla Haneef; Muhammad Raffi (Journal of Plant Pathology, 2025)

Chemical sensors for hazardous substances: advances in design, materials, and applications in environmental monitoring - Seyedeh Azadeh Alavi-Borazjani; Muhammad Noman Shafique (Environmental Monitoring and Assessment, 2025)

Synergistic Arsenic Adsorption by Nano Zero-Valent Iron and Biochar: Batch and Column Scale Performance - Muhammad Asif Naeem; Muhammad Imran; Muhammad Amjad; Ghulam Mustafa Shah; Ghulam Abbas; Behzad Murtaza; Muhammad Shafique Khalid; Hafiz Faiq Bakhat; Samina Khalid; Muhammad Imtiaz Rashid (Water, Air, & Soil Pollution, 2025)

Genomic and molecular characterization of TGF-beta superfamily in Parus major - Mehwish Sultana; Shakeela Parveen; Muhammad Farhan Khan; Muhammad Tayyab; Muhammad Hussain; Saman Shabir; Warda Safdar; Laiba Shafique (Organisms Diversity & Evolution, 2025)

Impact of Silicon Application on the Mineral Nutrient Profile and Fruit Quality of Mandarin Citrus Hybrid ‘Kinnow’ - Hafiz Faiq Bakhat; Muhammad Imran Razzaq; Muhammad Shafique Khalid; Sunaina Abbas; Natasha; Masood Iqbal Awan; Hasnain Anwar; Ghulam Mustafa Shah; Saira Afzal; Muhammad Rizwan Ashraf; Hafiz Mohkum Hammad (Applied Fruit Science, 2025)

Understanding flood behavior in the Kashmir Himalayas through copula-driven models - Ishfaq Gujree; Shafique ur Rehman; Joshal K. Bansal; Ningsheng Chen; Aijaz Ahmad Reshi; M. Sultan Bhat; Muhammad Atiq Ur Rehman Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Endophytic fungi as biocontrol agents: A metabolite-driven approach to crop protection and sustainable agriculture - Muhammad Faiq; Amjad Ali; Shazia Shafique; Sobiya Shafique; Allah Rakha Yaseen; Rimsha Fatima; Muhammad Tanveer Altaf; Faheem Shehzad Baloch (Physiological and Molecular Plant Pathology, 2025)

Insights into genetic diversity and chlorpyrifos resistance in fall armyworm Spodoptera frugiperda (Smith) population of Pakistan - Afia Shafique; Muhammad Sarwar; Naima Razzaq; Naveed Akhtar Shad; Saba Akram; Rubab Zahra Naqvi; Muhammad Asif (Phytoparasitica, 2025)

Achieving net-zero emissions in China’s building Sector: Critiques and strategies of minimizing embodied carbon - Wenshi Lin; Muhammad Shafique; Xiaowei Luo (Energy and Buildings, 2025)

Exploring the diversity and ethnomedicinal uses of wild edible plants in District Poonch, Azad Jammu and Kashmir - Amna Mustafa; Ansar Mehmood; Khawaja Shafique Ahmad; Sajjad Hussain; Muhammad Faraz Khan; Mushtaq Ahmad (Genetic Resources and Crop Evolution, 2025)

Phenological and morphological adaptations of Japanese quince (Chaenomeles japonica—(Thunb.)Lindl. ex Spach.) [Rosaceae]: insights from palynology and leaf histology - Shoxista Samatova; Mirtemir Berdiyev; Babir Baysunov; Muhammad Zafar; Salman Majeed; Mohamed Fawzy Ramadan; Trobjon Makhkamov; Muhammad Rizwan Khan; Khawaja Shafique Ahmad; Qamar Abbas; Ankeela Pńisyer; Fakhr ul Islam (Genetic Resources and Crop Evolution, 2025)

A novel Bi-weight Mid Correlation Coefficient Divergence (BMCCD) approach for multi-model ensemble-based drought assessment - Mahrukh Yousaf; Laraib Shafique; Sadia Qamar; Muhammad Shakeel; Farman Ali; Zulfiqar Ali (Environmental Monitoring and Assessment, 2025)

Survival strategies of shrubby seablite (Suaeda vera) for ecological success in hypersaline habitats - Naila Asghar; Zhen Liu; Amina Ameer; Khawaja Shafique Ahmad; Ummar Iqbal; Mansoor Hameed; Ying Shen; Zhao Hongxiang; Muhammad Kaleem; Tangyuan Ning (Journal of Environmental Management, 2025)

Morphometric analysis of debris flow hazard and risk assessment in the mountain terrains of northern Pakistan using remote sensing and field data - Nisar Ali Shah; Muhammad Shafique; Lewis A. Owen; Yaseen AI-Mulla; Yaseen Ullah (Earth Science Informatics, 2025)

Recent advancements in chemometrics based non-destructive analytical techniques for rapid detection of adulterants in milk and dairy products – A review - Rui Xu; Muhammad Zeeshan Adil; Sidra Jabeen; Khansa; Mahwish Tanveer; Sadia Younis; Bakhtawar Shafique; Long Li (Food Control, 2025)

Bio-metabolites Mechanism for the Eco-friendly Management of Alternaria Black Spot Disease Through the Use of Bio-agents in Canola - Effat Naz; Muhammad Jabran; Muhammad Bilal; Ikhlas Shafique; Farrukh Azeem; Amjad Abbas; Muhammad Amjad Ali (Journal of Crop Health, 2025)

Effect of Aloe Vera-Based Coating on Physicochemical and Phytochemical Properties of Wild Apricot Variety - Nazish Ashraf; Imran Hayat; Nagina Rafique; Khawaja Shafique Ahmad; Muhammad Zubair Khan; Khalid J. Alzahrani; Khalaf F. Alsharif (Applied Fruit Science, 2025)

Postharvest Treatment with ZnO and CuO Nanoparticles Improves Fruit Quality and Shelf Life of Guava Fruit - Muhammad Shafique Khalid; Samina Khalid; Noosheen Zahid; Mehdi Maqbool; Akif Safeen; Hafiz Faiq Bakhat; Muhammad Amjad; Behzad Murtaza (Applied Fruit Science, 2025)

Integrated landslide risk assessment utilizing open source satellite and ground data in the Himalayas of Northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain; Munawar Shah; Punyawi Jamjareegulgarn; Nassir Saad Alarifi; Mostafa R. Abukhadra (Natural Hazards, 2025)

Structural and functional traits driving Chloris flagellifera proliferation in arid saline environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad; Ansar Mehmood; Nargis Naz; Muhammad Akram (Acta Physiologiae Plantarum, 2025)

Molecular characterization of doublesex and Mab-3 (DMRT) gene family in Ctenopharyngodon idella (grass carp) - Shakeela Parveen; Muhammad Farhan Khan; Mehwish Sultana; Saif ur Rehman; Laiba Shafique (Journal of Applied Genetics, 2025)

Ecotoxicological investigation of arsenic contamination within the water-soil-fruit-human continuum - Muhammad Shafique Khalid; Nimra Farooq; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Samina Khalid; Hafiz Faiq Bakht; Ghulam Mustafa Shah; Muhammad Asif Naeem; Ghulam Abbas; Behzad Murtaza (Environmental Geochemistry and Health, 2025)

Optimization and partial purification of tannase from Bacillus licheniformis AS1 under submerged fermentation and its application - Aqsa Shafique; Hafiz Abdullah Shakir; Muhammad Irfan; Shaukat Ali; Muhammad Khan; Chaman Ara; Noor Khan (Systems Microbiology and Biomanufacturing, 2025)

Investigation of diabetes mellitus transmission in humans by using time delay tool and numerical treatment approach - Ali Raza; Ayesha Shabbir; Umar Shafique; Nauman Ahmed; Muhammad Rafiq (Modeling Earth Systems and Environment, 2025)

Policy impacts of intellectual property and academic research trends in marine-derived collagen and chitin/chitosan value chains - Helena Vieira; Mariana Almeida; Muhammad Noman Shafique; Miguel C. Leal; Ana I. Lillebø (Marine Policy, 2025)

Evaluating the safety and effectiveness of tolvaptan in patients with heart failure and renal impairment: a systematic review and meta-analysis - Aashish Kumar; Umer Iqbal; Shafin Bin Amin; Syed Ali Arsal; Syed Muhammad Sinaan Ali; Muhammad Ashir Shafique; Muhammad Saad Shahid; Aimen Naz; Emediong Santhus Asuka (European Journal of Clinical Pharmacology, 2025)

A multi-proxy approach to explore paleoenvironmental oscillations and chronostratigraphy of Thanetian carbonates in Eastern Tethys, Pakistan - Amir Shahzad; Yasir Sirfraz; Khawaja Shoaib Ahmed; Muhammad Hanif; Muhammad Tayyib Riaz; Khawaja Shafique Ahmad; Thierry Adatte (Marine and Petroleum Geology, 2025)

Potential interventions and interactions of bioactive polyphenols and functional polysaccharides to alleviate inflammatory bowel disease – A review - Muhammad Salman Farid; Bakhtawar Shafique; Rui Xu; Łukasz Łopusiewicz; Changhui Zhao (Food Chemistry, 2025)

Dynamic lifecycle emissions of electric and hydrogen fuel cell vehicles in a multi-regional perspective - Fangjie Liu; Muhammad Shafique; Xiaowei Luo (Environmental Impact Assessment Review, 2025)

Integrated debris flow hazard and risk assessment using UAV data and RAMMS, a case study in northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain; Israr Ullah (Natural Hazards, 2025)

An integrated approach for GLOF hazard, vulnerability and risk assessment in the Karakoram Mountain Range of northern Pakistan - Sajid Ullah; Muhammad Shafique; Ghazanfar Ali Khattak; Attaullah Shah; Yaseen Ullah (Journal of Mountain Science, 2025)

Modulations in Physiological and Biochemical attributes of Citrus Limon by selenium nanoparticles (SeNPs) under salinity stress - Hummera Nawaz; Khawaja Shafique Ahmad; Iqra Aslam; Athar Mahmood; Ansar Mehmood; Ameer Khan; Muhammad Jamil; Amina Ameer; Muhammad Faraz Khan; Sajjad Hussain (Biocatalysis and Agricultural Biotechnology, 2024)

A homozygous missense variant in YTHDC2 induces azoospermia in two siblings - Shixiong Tian; Muhammad Faheem; Humayoon Shafique Satti; Jianqiu Xiao; Feng Zhang; Tahir Naeem Khan; Chunyu Liu (Molecular Genetics and Genomics, 2024)

Exome sequencing in four families with neurodevelopmental disorders: genotype–phenotype correlation and identification of novel disease-causing variants in VPS13B and RELN - Tehseen Ullah Khan Afridi; Ambrin Fatima; Humayoon Shafique Satti; Zaineb Akram; Imran Khan Yousafzai; Wajahat Bin Naeem; Nasreen Fatima; Asmat Ali; Zafar Iqbal; Ayaz Khan; Muhammad Shahzad; Chunyu Liu; et al. (Molecular Genetics and Genomics, 2024)

Bridging drug discovery through hierarchical subtractive genomics against asd, trpG, and secY of pneumonia causing MDR Staphylococcus aureus - Ayesha Wisal; Nida Saeed; Muhammad Aurongzeb; Muhammad Shafique; Saman Sohail; Waheed Anwar; Zarrin Basharat; Muhammad Irfan; Asad Ullah; Syed S. Hassan (Molecular Genetics and Genomics, 2024)

Debris flow simulations for hazard, vulnerability and risk assessment in the Karakorum mountain ranges, northern Pakistan - Israr Ullah; Muhammad Shafique; Ghazanfar Ali Khattak; Attaullah Shah (Remote Sensing Applications: Society and Environment, 2024)

Hydro-geochemistry and age-dependent health risk assessment of nitrate, nitrite, and fluoride in health facilities water: a multivariate analysis - Areej Nadeem; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Muhammad Shahid; Abdullah Ghardan Al-Sehemi; Yasar Nelliyot Kavil; Muhammad Amjad; Muhammad Wakeel (Environmental Science and Pollution Research, 2024)

Green synthesis of silver nanoparticles for antifungal activity against tomato fusarium wilt caused by Fusarium oxysporum - Raja Zaheer Tabassum; Ansar Mehmood; Abd ur Rehman Khalid; Khawaja Shafique Ahmad; Muhammad Abdul Rauf Khan; Muhammad Shoaib Amjad; Muhammad Raffi; Gull-e-laala Khan; Amna Mustafa (Biocatalysis and Agricultural Biotechnology, 2024)

Anatomical and Ionomics Investigation of Bread Wheat (Triticum aestivum L.) to Decipher Tolerance Mechanisms Under Arsenic Stress - Muhammad Anas; Muhammad Saeed; Kashif Naeem; Munib Ahmed Shafique; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2024)

High-resolution landslide mapping and susceptibility assessment: Landslide temporal variations and vegetation recovery - Muhammad Zeeshan Ali; Kejie Chen; Muhammad Shafique; Muhammad Adnan; Zhiwen Zheng; Wei Zhang; Zhanhui Qing (Advances in Space Research, 2024)

Retraction Note: Post-COVID-19’s impact on green supply chain management and sustainable E-commerce performance: the moderating role of big data analytics - Fazila Jalil; Jianhua Yang; Shafique Ur Rehman; Muhammad Mohid Khan (Environmental Science and Pollution Research, 2024)

Quantifying delayed climate mitigation benefits in electric and hydrogen fuel cell vehicle deployment for sustainable mobility - Fangjie Liu; Muhammad Shafique; Xiaowei Luo (Sustainable Production and Consumption, 2024)

Molecular identification and characterization of iris yellow spot virus (IYSV) and garlic virus X (GVX) infecting Allium species - Muhammad Usman Shahid; Abid Riaz; Tahira Shafique; Mayasar I. Al-zaban; Diaa Abd El-Moneim; Sheikh Mansoor; Yong Suk Hung; Hyeon-Jin Sun (Plant Biotechnology Reports, 2024)

Microsatellite and mtDNA-based exploration of inter-generic hybridization and patterns of genetic diversity in major carps of Punjab, Pakistan - Shakeela Parveen; Khalid Abbas; Muhammad Tayyab; Muhammad Hussain; Huma Naz; Laiba Shafique (Aquaculture International, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Green synthesis of silver nanoparticles for their antifungal activity against anthracnose disease causing Colletotrichum capsici - Anum Haq Nawaz; Ansar Mehmood; Abd ur Rehman Khalid; Muhammad Abdul Rauf Khan; Gul-e-lala; Khawaja Shafique Ahmad; Asad Ghulam Nabi (Biocatalysis and Agricultural Biotechnology, 2024)

Genetic characterization, structural analysis, and detection of positive selection in small heat shock proteins of Cypriniformes and Clupeiformes - Mehwish Sultana; Muhammad Tayyab; Shakeela Parveen; Muhammad Hussain; Laiba Shafique (Fish Physiology and Biochemistry, 2024)

Multiple Transgenic Strategies Positively Regulate Cold-Induced Sweetening in Low Temperature Stored Potato Tubers - Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Shazia Shafique; Nusrat Jahan; Muhammad Umar Bhatti; Rida Khalid; Ayman Naeem; Qamar Abbas; Sobiya Shafique; Bushra Tabassum (Potato Research, 2024)

Light-duty passenger vehicle electrification in China from 2021 to 2050 and associated greenhouse gas emissions: A dynamic fleet perspective - Bin Shui; Muhammad Shafique; Xiaowei Luo (Transportation Research Part D: Transport and Environment, 2024)

Local-scale integrated seismic risk assessment using satellite data and field information in Northern Pakistan - Tanveer Ahmed; Khaista Rehman; Muhammad Shafique; Nisar Ali Shah; Muhammad Waqar Azeem (Stochastic Environmental Research and Risk Assessment, 2024)

Natural esters as sustainable alternating dielectric liquids for transformer insulation system: analyzing the state of the art - Muhammad Rafiq; Muhammad Shafique; Muhammad Ateeq; Markus Zink; Deniz Targitay (Clean Technologies and Environmental Policy, 2024)

2-Hydroxybenzohydrazide as a novel potential candidate against nociception, inflammation, and pyrexia: in vitro, in vivo, and computational approaches - Gowhar Ali; Nazar Ul Islam; Muhammad Qaim; Rahim Ullah; Muhammad Saeed Jan; Khadija Shabbiri; Muhammad Shafique; Muhammad Ayaz (Inflammopharmacology, 2024)

WITHDRAWN: Valorization of Algal Biomass to Synthesize Heterogeneous gCN-Biochar Photocatalyst for the Treatment of Industrial Wastewater using Photocatalysis-Persulfate Oxidation Process - Aqsa Shafique; Hafiz Muhammad Uzair Ayub; Javed Iqbal; Shanawar Hamid; Fawad Ashraf; Muhammad Saif Ur Rehman; S. Boukhari; Mohamed A. Habila; Alam Nawaz; Tahir Fazal (Chemosphere, 2024)

Detection of high-risk human papillomavirus infected cervical biopsies samples by immunohistochemical expression of the p16 tumor marker - Muhammad Shafique; Iqra Shoaib; Bilal Aslam; Rabia Khalid; Imrana Tanvir; Muhammad Hidayat Rasool; Tawaf Ali Shah; Khalid S. Almaary; Mohammed Bourhia; Muhammad Usman Qamar (Archives of Microbiology, 2024)

Biowaste-based sorbents for arsenic removal from aqueous medium and risk assessment - Maham Akhtar Nagra; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Rabia Naz; Sabah Ansar; Muhammad Shahid; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Nasir Masood; Ghulam Mustafa Shah; et al. (Environmental Geochemistry and Health, 2023)

Prospects of recycling from end-of-life of Li-ion batteries on alleviating materials demand-supply gap in new electric vehicles in Asia - Muhammad Shafique; Muhammad Ateeq; Muhammad Rafiq; Anam Azam; Xiaowei Luo (Waste Management, 2023)

Advancements and challenges in phytochemical-mediated silver nanoparticles for food packaging: Recent review (2021–2023) - Shujat Ali; Xiaojing Chen; Shujaat Ahmad; Wahid Shah; Muhammad Shafique; Pramila Chaubey; Gulam Mustafa; Amal Alrashidi; Sitah Alharthi (Trends in Food Science & Technology, 2023)

Survival tactics of an endangered species Withania coagulans (Stocks) Dunal to arid environments - Ummar Iqbal; Fahad Ur Rehman; Muhammad Usama Aslam; Muhammad Faisal Gul; Umar Farooq; Amina Ameer; Naila Asghar; Ansar Mehmood; Khawaja Shafique Ahmad (Environmental Monitoring and Assessment, 2023)

Therapeutic Potential of Selenium Nanoparticles on Letrozole-Induced Polycystic Ovarian Syndrome in Female Wistar Rats - Maisra Azhar Butt; Hafiz Muhammad Shafique; Mahjabeen Mustafa; Nurain Baig Moghul; Anum Munir; Urwah Shamas; Sobia Tabassum; Mubin Mustafa Kiyani (Biological Trace Element Research, 2023)

Variations of b-value and the ω-upper bound magnitude of GIII distribution of the Pamir–Hindu Kush region - Khaista Rehman; Wajid Ali; Muhammad Shafique; Aamir Ali; Adnan Barkat; Waqas Ahmed; Muhammad Waqar Azeem (Arabian Journal of Geosciences, 2023)

Post-COVID-19’s impact on green supply chain management and sustainable E-commerce performance: the moderating role of big data analytics - Fazila Jalil; Jianhua Yang; Shafique Ur Rehman; Muhammad Mohid Khan (Environmental Science and Pollution Research, 2023)

Investigating catalytic oxidative desulfurization of model fuel using hollow PW12/TiO2@MgCO3 and performance optimization via box-behnken design - Sadaf Ul Hassan; Hamna Khalid; Sidra Shafique; Muhammad Asim Farid; Muhammad Haris Saeed; Zulfiqar Ali; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Food waste: causes and economic losses estimation at household level in Pakistan - Samina Khalid; Aman Ullah Malik; Muhammad Irfan Ullah; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Asif Naeem; Aqsa Naseer (Environmental Science and Pollution Research, 2023)

Effective citric acid and EDTA treatments in cadmium stress tolerance in pepper (Capsicum annuum L.) seedlings by regulating specific gene expression - Rana M. Alshegaihi; Manar Fawzi Bani Mfarrej; Muhammad Hamzah Saleem; Abida Parveen; Khawaja Shafique Ahmad; Baber Ali; Amany H.A. Abeed; Dikhnah Alshehri; Sameera A. Alghamdi; Suliman M.S. Alghanem; Javeed Ahmad Lone; Tarek M.A. Soliman; et al. (South African Journal of Botany, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Aridity-driven changes in structural and physiological characteristics of Buffel grass (Cenchrus ciliaris L.) from different ecozones of Punjab Pakistan - Amina Ameer; Farooq Ahmad; Naila Asghar; Mansoor Hameed; Khawaja Shafique Ahmad; Ansar Mehmood; Fahim Nawaz; Muhammad Asif Shehzad; Sahar Mumtaz; Muhammad Kaleem; Ummar Iqbal (Physiology and Molecular Biology of Plants, 2023)

Microbial biochemical pathways of arsenic biotransformation and their application for bioremediation - Hareem Mohsin; Maria Shafique; Muhammad Zaid; Yasir Rehman (Folia Microbiologica, 2023)

Genome resource of Xanthomonas oryzae pv. oryzae Chinese strain NE-8 causing bacterial blight of rice - Muhammad Sohaib Shafique; Wei Guo; Xifeng Chen; Kaijun Zhao; Yapei Liu; Chunlian Wang; Zhiyuan Ji (Functional & Integrative Genomics, 2023)

Modification in cellulose films through ascent cold plasma treatment and polymerization for food products packaging - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Rana Muhammad Aadil; Muhammad Faisal Manzoor; Jun-Hu Cheng (Trends in Food Science & Technology, 2023)

Optimization of Citric Acid and EDTA Levels Under Ni Stress Using Rapeseed Brassica napus L. for Phytoremediation - Humera Nawaz; Naila Asghar; Aamir Ali; Amina Ameer; Muhammad Asif Shehzad; Fahim Nawaz; Ansar Mehmood; Muhammad Sajjad Iqbal; Ummar Iqbal; Muhammad Kaleem; Ameer Khan; Khawaja Shafique Ahmad (Water, Air, & Soil Pollution, 2023)

Reconnoitering the capabilities of nodule endophytic Pantoea dispersa for improved nodulation and grain yield of chickpea (Cicer arietinum L.) - Mohsin Tariq; Nayab Hasnain; Ijaz Rasul; Muhammad Azeem Asad; Aqsa Javed; Kamran Rashid; Javeria Shafique; Wajeeha Iram; Amir Hameed; Marriam Zafar (World Journal of Microbiology and Biotechnology, 2023)

Biochar Amendment in Combination with Endophytic Bacteria Stimulates Photosynthetic Activity and Antioxidant Enzymes to Improve Soybean Yield Under Drought Stress - Fahim Nawaz; Rashid Rafeeq; Sadia Majeed; Muhammad Shoaib Ismail; Muhammad Ahsan; Khawaja Shafique Ahmad; Ahsan Akram; Ghulam Haider (Journal of Soil Science and Plant Nutrition, 2023)
The beneficial effects of biochar (BC) and plant growth-promoting bacteria (PGPR) to increase crop yields under harsh environments have been widely reported. However, the knowledge on the synergistic effects of BC and PGPR to induce drought tolerance in oilseeds is scant. In the present study, the effects of cotton sticks derived BC together with PGPR strains ( Paraburkholderia phytofirmans and Bacillus sp.) were examined in water-stressed soybean plants. Initially, the BC application rates (1% and 2%) for soybean were optimized in a pilot experiment (experiment I), and the most effective level (1%) was selected for further studies together with PGPR in the second experiment. The soybean plants were raised in pots under semi-controlled conditions and were subjected to drought stress (25–30% water holding capacity) at pod formation stage. In comparison with control, the drought-mediated decrease in photosynthetic pigments and gas exchange characteristics was markedly lower in BC and PGPR-treated plants. However, the maximum increase in photosynthetic (12–30%) and the enzymatic antioxidant activities (5–20%) was recorded in plants treated with BC + P. phytofirmans , whereas no further significant increase was observed in plants treated with combined BC and Bacillus sp. under water deficit conditions. Similarly, the combined BC and P. phytofirmans application considerably increased the grain yield (14%) under drought stress conditions. We conclude that the combined application of BC + P. phytofirmans could be utilized as an effective strategy to improve soybean yield in dry arid regions.

Estimation of glacier mass balance using remote sensing and GIS technology in the Hindu Kush region of northern Pakistan - Sidra Bibi; Muhammad Shafique; Neelum Ali; Shahla Nazneen; Liaqat Ali; Siddique Ullah Baig; Rehman Gul (Earth Science Informatics, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Porous Ag3VO4/KIT-6 composite: Synthesis, characterization and enhanced photocatalytic performance for degradation of Congo Red - Iqra Mahboob; Iqrash Shafiq; Sumeer Shafique; Parveen Akhter; Mamoona Munir; Muhammad Saeed; Muhammad Shahid Nazir; Um-e-Salma Amjad; Farrukh Jamil; Nabeel Ahmad; Young-Kwon Park; Murid Hussain (Chemosphere, 2023)

Hydrogen Production through Water Vapors using Optimized Corona-DBD Hybrid Plasma Micro-Reactor - Muhammad Younas; Sumeer Shafique; Abrar Faisal; Ainy Hafeez; Fahed Javed; Maria Mustafa; Fahad Rehman (Fuel, 2023)

Correction to: Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

NGS-driven molecular diagnosis of heterogeneous hereditary neurological disorders reveals novel and known variants in disease-causing genes - Ayaz Khan; Shixiong Tian; Muhammad Tariq; Sheraz Khan; Muhammad Safeer; Naimat Ullah; Nazia Akbar; Iram Javed; Mahnoor Asif; Ilyas Ahmad; Shahid Ullah; Humayoon Shafique Satti; et al. (Molecular Genetics and Genomics, 2022)

Spatio-temporal landslide inventory and susceptibility assessment using Sentinel-2 in the Himalayan mountainous region of Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff; Mark van der Meijde; Mian Luqman Hussain; Sohail Wahid (Environmental Monitoring and Assessment, 2022)

Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Porostereum spadiceum-AGH786 Regulates the Growth and Metabolites Production in Triticum aestivum L. Under Salt Stress - Syeda Leeda Gul; Yong-Sun Moon; Muhammad Hamayun; Sumera Afzal Khan; Amjad Iqbal; Muhammad Aaqil Khan; Anwar Hussain; Maryam Shafique; Yoon-Ha Kim; Sajid Ali (Current Microbiology, 2022)

Survival strategies in two high altitude Sorghum species from western Himalayas - Khwaja Shafique Ahmad; Anum Javaid; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Ashraf; Syed Mohsan Raza Shah; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad (Acta Physiologiae Plantarum, 2022)

Endophytic aspergillus oryzae reprograms Abelmoschus esculentus L. to higher growth under salt stress via regulation of physiochemical attributes and antioxidant system - Farzana Gul Jan; Nusrat bibi; Muhammad Hamayun; Yong-Sun Moon; Gul Jan; Maryam Shafique; Sajid Ali (Biologia, 2022)

Applications of Biotechnology in Food and Agriculture: a Mini-Review - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Waseem Khalid; Hafiz Rehan Nadeem; Ghulam Mueen-ud-Din; Muhammad Zubair Khalid (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Correction to: First report of Alternaria alternata causing post‑harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

First report of Alternaria alternata causing post-harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

Correction to: Lineament mapping for a part of the central Sulaiman fold–Thrust Belt (SFTB), Pakistan - Ali Abbas Wajid; Muhammad Anees; Shams ul Alam; Jodat Kamran Gorchani; Khurram Shahzad; Asif Israr; Muhammad Shafique (Arabian Journal of Geosciences, 2021)

Sulfate-Based Fertilizers Regulate Nutrient Uptake, Photosynthetic Gas Exchange, and Enzymatic Antioxidants to Increase Sunflower Growth and Yield Under Drought Stress - Bilal Ahamid Shafiq; Fahim Nawaz; Sadia Majeed; Muhammad Aurangzaib; Abdullah Al Mamun; Muhammad Ahsan; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muqarrab Ali; Sarfraz Hashim; Tanveer ul Haq (Journal of Soil Science and Plant Nutrition, 2021)
The challenging impact of drought to agricultural productivity requires the adoption of mitigation strategies with a better understanding of underlying mechanisms responsible for drought tolerance. The present study aimed at investigating the effects of sulfur-based fertilizers on mitigation of drought stress in sunflower. Sulfate-containing fertilizers, viz., ammonium sulfate, zinc sulfate, magnesium sulfate, potassium sulfate, and gypsum, were initially evaluated at two different rates (10 and 20 mg kg −1 soil equivalent to 20 and 40 kg ha −1 , respectively) for nutrient uptake and growth-promoting traits in sunflower seedlings (cv. Hysun-33). The best performing fertilizer (gypsum) was then selected to evaluate the response of sunflower under drought stress imposed at flowering stage for three weeks (25–30% water holding capacity). Results indicated significant amelioration of drought stress with higher activity of photosynthetic apparatus, upregulation of antioxidative enzymes, and increased achene yield by gypsum application. In comparison to control, gypsum-treated plants (20 mg kg −1 soil) exhibited higher water status (32%), leaf photosynthetic rate (29%), transpiration rate (67%), and stomatal conductance (118%) under drought stress. The antioxidant enzyme activities of catalase, guaiacol peroxidase, and superoxide dismutase were also increased by 67%, 62%, and 126%, respectively, resulting in higher achene yield (19%) under water-deficit conditions. This study indicates that the application of sulfur-based fertilizers (gypsum) can be used to induce drought tolerance and obtain high sunflower yields under drought stress, and furthermore, it is a cost-effective strategy resulting in high benefit–cost ratio with respect to no gypsum application.

Combining Landsat-8 spectral bands with ancillary variables for land cover classification in mountainous terrains of northern Pakistan - Arif Ur Rehman; Sami Ullah; Muhammad Shafique; Muhammad Sadiq Khan; Muhammad Tariq Badshah; Qi-jing Liu (Journal of Mountain Science, 2021)

Landslide assessment by using multi-temporal UAV datasets: a case study in northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain (Arabian Journal of Geosciences, 2021)

Lineament mapping for a part of the Central Sulaiman Fold–Thrust Belt (SFTB), Pakistan - Ali Abbas Wajid; Muhammad Anees; Shams ul Alam; Jodat Kamran Gorchani; Khurram Shahzad; Asif Israr; Muhammad Shafique (Arabian Journal of Geosciences, 2021)
This study aims to analyze the lineaments using the field data and a remote sensing approach, to describe their relationship with the folds, faults, and regional tectonic stress of the central Sulaiman Fold-Thrust Belt. Joint data, from nine anticlines, has been collected using the scanline method and classified into three sets (JS1, JS2, and JS3) based on their geometrical relationships. Lineaments extracted from the 30 m digital elevation model have been classified subsequently into three lineament sets (LS1, LS2, and LS3) based on the azimuths from the corresponding joint sets. A very high correlation coefficient (rs = 0.97), between the azimuths of the field joints and the remotely sensed lineaments, has been observed which validates that the lineaments are the regional representation of the local field joints. The geometrical relationship of the lineament sets with the fold hinges indicates that the older LS1 and LS2 are strongly related to the regional folding episode, while the younger LS3 is a result of local shears. The chronological interpretation of the deformational events responsible for the lineament sets is constrained by the presence of the Kingri Fault, which induces a strike-slip component within the study area. Furthermore, the controls on the joint and lineament sets, established using multivariate statistics to decipher the effects of lithological and structural contrasts on the lineament density, reveal that an increase in the lineament density can be attributed to the competence and thickness of the rock units as well as the variable local stresses across the different folds. Based on the orientations of these lineament sets, the cumulative direction of the compressive event in the NW-SE direction (310–320) coincides with the regional stress direction of the SFTB.

Correction to: Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan - Bushra Rashid; Muhammad Zubair; Nausheen Irshad; Khawaja Shafique Ahmad; Majid Mahmood; Majid Mahmood Tahir; Khizar Hussain Shah; Aqeela Shaheen (Bulletin of Environmental Contamination and Toxicology, 2021)

Physiological insights into sulfate and selenium interaction to improve drought tolerance in mung bean - Muhammad Aqib; Fahim Nawaz; Sadia Majeed; Abdul Ghaffar; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muhammad Naeem Tahir; Muhammad Aurangzaib; Hafiz Muhammad Rashad Javeed; Muhammad Habib-ur-Rahman; Muhammad Munir Usmani (Physiology and Molecular Biology of Plants, 2021)
The present study involved two pot experiments to investigate the response of mung bean to the individual or combined SO 4 2− and selenate application under drought stress. A marked increment in biomass and NPK accumulation was recorded in mung bean seedlings fertilized with various SO 4 2− sources, except for CuSO 4 . Compared to other SO 4 2− fertilizers, ZnSO 4 application resulted in the highest increase in growth attributes and shoot nutrient content. Further, the combined S and Se application (S + Se) significantly enhanced relative water content (16%), SPAD value (72%), photosynthetic rate (80%) and activities of catalase (79%), guaiacol peroxidase (53%) and superoxide dismutase (58%) in the leaves of water-stressed mung bean plants. Consequently, the grain yield of mung bean was markedly increased by 105% under water stress conditions. Furthermore, S + Se application considerably increased the concentrations of P (47%), K (75%), S (80%), Zn (160%), and Fe (15%) in mung bean seeds under drought stress conditions. These findings indicate that S + Se application potentially increases the nutritional quality of grain legumes by stimulating photosynthetic apparatus and antioxidative machinery under water deficit conditions. Our results could provide the basis for further experiments on cross-talk between S and Se regulatory pathways to improve the nutritional quality of food crops.

Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan - Bushra Aziz; Muhammad Zubair; Nausheen Irshad; Khawaja Shafique Ahmad; Majid Mahmood; Majid Mahmood Tahir; Khizar Hussain Shah; Aqeela Shaheen (Bulletin of Environmental Contamination and Toxicology, 2021)
The current study was designed to determine the concentrations of toxic metals (Ni, Pb and Cr) in feathers of birds collected from four regions of NE Pakistan. Feather samples of birds (House Crow, Common Myna and House Sparrow) were collected from different areas. Atomic absorption spectrophotometer was used to determine the concentration of metals in feathers. Analysis of the data revealed that concentrations of Pb and Cr were significantly different ( p < 0.05) among bird species, whereas no difference ( p > 0.05) was detected among bird species (house crow, common myna and house sparrow) for Ni. A significant difference was found for the concentration of Pb and Ni in all the four studied regions. Whereas, non-significant difference was found in all the studied regions for the concentrating of Cr. It was revealed that there is significant rising concentration of metals (Pb, Cr) in feathers of birds in Azad Kashmir.

Landslide inventory and susceptibility assessment using multiple statistical approaches along the Karakoram highway, northern Pakistan - Mian Luqman Hussain; Muhammad Shafique; Alam Sher Bacha; Xiao-qing Chen; Hua-yong Chen (Journal of Mountain Science, 2021)

Scenario-based seismic hazard analysis using spectral element method in northeastern Pakistan - Saad Khan; Mark van der Meijde; Harald van der Werff; Muhammad Shafique (Natural Hazards, 2020)
Seismic hazard analysis is carried out in this study by estimating ground motion for hypothetical earthquakes in the area of Muzaffarabad, Pakistan, with the MT solution of the 2005 Kashmir earthquake. The earth’s topography influences seismic waves by scattering and reflecting it, thereby causing spatial variation in seismic response. Using the moment tensor solution of the 2005 Kashmir earthquake, we perform 25 spectral element method (SEM)-based 3D simulations along major faults in the study area. The SEM model incorporates the topography and homogeneous half-space characteristics. Our results show that, beside topography, the relative location of the source with respect to slopes also has an influence on the observed variation in ground shaking amplitudes. By integrating the mean and standard deviation of estimated ground shaking from 25 simulations, we present a seismic hazard map for the study area. The map summarizes the topographic and potential source location effect on seismic-induced ground shaking in the study area. It provides a classification from hazardous to safe in relative terms and can be used as a guide in earthquake preparedness.

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Transferability of object-based image analysis approaches for landslide detection in the Himalaya Mountains of northern Pakistan - Alam Sher Bacha; Harald Van Der Werff; Muhammad Shafique; Hawas Khan (International Journal of Remote Sensing, 2020)

Implication of Physiological and Biochemical Variables of Prognostic Importance in Lead Exposed Subjects - Arif Malik; Muhammad Abdul Basit Ashraf; Muhammad Waqas Khan; Ayesha Zahid; Hassan Shafique; Sulayman Waquar; Siew Hua Gan; Muhammad Ashraf (Archives of Environmental Contamination and Toxicology, 2020)

ASTER-based remote sensing investigation of gypsum in the Kohat Plateau, north Pakistan - Asad Khan; Shah Faisal; Muhammad Shafique; Saad Khan; Alam Sher Bacha (Carbonates and Evaporites, 2020)

Adaptations in Imperata cylindrica (L.) Raeusch. and Cenchrus ciliaris L. for altitude tolerance - Khawaja Shafique Ahmad; Ambreen Wazarat; Ansar Mehmood; Muhammad Sajid Aqeel Ahmad; Majid Mahmood Tahir; Fahim Nawaz; Haroon Ahmed; Mohsin Zafar; Aneela Ulfat (Biologia, 2020)

Correction to: Flood hazard assessment and mapping of River Swat using HEC-RAS 2D model and high-resolution 12-m TanDEM-X DEM (WorldDEM) - Muhammad Farooq; Muhammad Shafique; Muhammad Shahzad Khattak (Natural Hazards, 2019)

Flood hazard assessment and mapping of River Swat using HEC-RAS 2D model and high-resolution 12-m TanDEM-X DEM (WorldDEM) - Muhammad Farooq; Muhammad Shafique; Muhammad Shahzad Khattak (Natural Hazards, 2019)

Synthesis of new chiral 1,3,4-thiadiazole-based di- and tri-arylsulfonamide residues and evaluation of in vitro anti-HIV activity and cytotoxicity - Maria Shafique; Shahid Hameed; Muhammad Moazzam Naseer; Najim Aboud Al-Masoudi (Molecular Diversity, 2018)

Regolith thickness modeling using a GIS approach for landslide distribution analysis, NW Himalayas - Muhammad Basharat; Masood Qasim; Muhammad Shafique; Nasir Hameed; Muhammad Tayyib Riaz; Muhammad Rustam Khan (Journal of Mountain Science, 2018)

An international program on Silk Road Disaster Risk Reduction–a Belt and Road initiative (2016–2020) - Lei Yu; Cui Peng; Amar Deep Regmi; Virginia Murray; Alessandro Pasuto; Giacomo Titti; Muhammad Shafique; Tilak Priyadarshana D. G (Journal of Mountain Science, 2018)

Landslide inventory and susceptibility modelling using geospatial tools, in Hunza-Nagar valley, northern Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff (Journal of Mountain Science, 2018)

Geology as a proxy for Vs30-based seismic site characterization, a case study of northern Pakistan - Muhammad Shafique; Mian Luqman Hussain; M. Asif Khan; Mark van der Meijde; Sarfraz Khan (Arabian Journal of Geosciences, 2018)

Flood frequency analysis of river swat using Log Pearson type 3, Generalized Extreme Value, Normal, and Gumbel Max distribution methods - Muhammad Farooq; Muhammad Shafique; Muhammad Shahzad Khattak (Arabian Journal of Geosciences, 2018)

Effects of nickel toxicity on morphological and physiological aspects of osmoregulation in Typha domingensis (Typhaceae) populations - Noreen Akhtar; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Khawaja Shafique Ahmad; Jiabin Deng; Ansar Mehmood; Claudia Segovia-Salcedo; Muhammad Muslim Shahnaz; Abdul Qadir Khan (Limnology, 2018)

Sensitivity to house dust mite allergens and prevalence of allergy-causing house dust mite species in Pothwar, Pakistan - Rubaba Hamid Shafique; Shamim Akhter; Shahid Abbas; Muhammad Ismail (Experimental and Applied Acarology, 2018)

Beating cold by being tough: impact of elevation on leaf characteristics in Phleum himalaicum Mez. endemic to Himalaya - Khawaja Shafique Ahmad; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Bushra Hafeez Kiani; Muhammad Sajid Aqeel Ahmad; Jiabin Deng; Farooq Ahmad; Imtiaz Hussain; Sana Fatima (Acta Physiologiae Plantarum, 2018)

Evaluating the impact of classification algorithms and spatial resolution on the accuracy of land cover mapping in a mountain environment in Pakistan - Sami Ullah; Muhammad Shafique; Muhammad Farooq; Muhammad Zeeshan; Matthias Dees (Arabian Journal of Geosciences, 2017)

Applications of variogram modeling to electrical resistivity data for the occurrence and distribution of saline groundwater in Domail Plain, northwestern Himalayan fold and thrust belt, Pakistan - Asam Farid; Perviez Khalid; Klian Zaib Jadoon; Muhammad Asim Iqbal; Muhammad Shafique (Journal of Mountain Science, 2017)

Spatial assessment of forest cover and land-use changes in the Hindu-Kush mountain ranges of northern Pakistan - Sami Ullah; Muhammad Farooq; Muhammad Shafique; Muhammad Afra Siyab; Fazli Kareem; Matthias Dees (Journal of Mountain Science, 2016)

Morpho-anatomical and physiological adaptations to high altitude in some Aveneae grasses from Neelum Valley, Western Himalayan Kashmir - Khawaja Shafique Ahmad; Mansoor Hameed; Sana Fatima; Muhammad Ashraf; Farooq Ahmad; Mehwish Naseer; Noreen Akhtar (Acta Physiologiae Plantarum, 2016)

Impact of uncertainty in remote sensing DEMs on topographic amplification of seismic response and Vs 30 - Muhammad Shafique; Mark van der Meijde (Arabian Journal of Geosciences, 2015)

A Spatial Multi-Criteria Analysis Approach for Locating Suitable Sites for Construction of Subsurface Dams in Northern Pakistan - Imran Ali Jamali; Ulla Mörtberg; Bo Olofsson; Muhammad Shafique (Water Resources Management, 2014)

Investigating the concurrent presence of HCV in serum, oral fluid and urine samples from chronic HCV patients in Faisalabad, Pakistan - Muhammad Shafique; Nasir Ahmad; Fazli R. Awan; Tanveer Mustafa; Mujib Ullah; Javed A. Qureshi (Archives of Virology, 2009)